USE OF HUMAN MILK FORTIFIERS IN PRETERM INFANTS – STRATEGIES, BENEFITS AND CLINICAL SIGNIFICANCE: A LITERATURE REVIEW - Alicja Stryczek-Schlusche,; Oliwia Gugała,; Kamil Nowak,; Hanna Paszkiewicz,; Patryk Kowalczyk,; Bartłomiej Trzciński,; Igor Winogrodzki,; Aleksandra Magdalena Furczyńska,; Filip Bracichowicz,; Aleksandra Gęsińska, (International Journal of Innovative Technologies in Social Science, 2025)
In Poland, 7–8% of newborns are born preterm, a condition linked to a range of health complications. Adequate nutrition plays a vital role in caring for preterm infants, fostering growth and development and helping prevent metabolic complications. Although breast milk is the optimal source of nutrients and immunological factors, its composition may not fully meet the increased nutritional demands of preterm infants. In such cases, human milk fortifiers (HMFs) are used to provide additional protein, energy, minerals, and vitamins. This article reviews the different types of HMFs, their nutritional composition, and the guidelines for their use. The benefits of fortification are also presented, including improved weight gain, better bone mineralization, and prevention of nutritional deficiencies. HMFs are well tolerated and safe, and their use constitutes an important element of enteral nutrition in preterm infants.